The role of Actopaxin in tumor metastasis. (November 2022) - Qu, Manrong; Yu, Kehui; Rehman Aziz, Aziz Ur; Zhang, Hangyu; Zhang, Zhengyao; Li, Na; Liu, Bo
Abstract: Actopaxin is a newly discovered focal adhesions (FAs) protein, actin-binding protein and pseudopodia-enriched molecule. It can not only bind to a variety of FAs proteins (such as Paxillin, ILK and PINCH) and non-FAs proteins (such as TESK1, CdGAP, β2-adaptin, G3BP2, ADAR1 and CD29), but also participates in multiple signaling pathways. Thus, it plays a crucial role in regulating important processes of tumor metastasis, including matrix degradation, migration, and invasion, etc. This review covers the latest progress in the structure and function of Actopaxin, its interaction with other proteins as well as its involvement in regulating tumor development and metastasis. Additionally, the current limitations for Actopaxin related studies and the possible research directions on it in the future are also discussed. It is hoped that this review can assist relevant researchers to obtain a deep understanding of the role that Actopaxin plays in tumor progression, and also enlighten further research and development of therapeutic approaches for the treatment of tumor metastasis.